Pemberdayaan Pendidikan Berkelanjutan untuk Meningkatkan Kemandirian Pembelajaran dengan Literasi Digital di Desa - Hafizah Ali; Solfema Solfema; Lili Dasa Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
Sustainable education plays a crucial role in enhancing independent learning among rural communities in the digital era. This article discusses the importance of sustainable education models in empowering rural populations to adapt to technological advancements. With limited access to formal education, many rural communities benefit from continuous education programs that equip them with relevant skills and knowledge. The implementation of digital-based education models facilitates flexible learning and encourages self-directed learning, allowing individuals to access educational resources from their homes. Furthermore, developing digital literacy skills is essential for rural residents to effectively utilize technology for learning purposes. This article also explores strategies for technology-based teaching that enhance the learning experience and ensure that educational materials are accessible and engaging. Ultimately, the findings indicate that sustainable digital education can significantly improve the skills and knowledge of rural communities, fostering a culture of lifelong learning and independence.